2002
DOI: 10.1104/pp.005587
|View full text |Cite
|
Sign up to set email alerts
|

Successive Glycosyltransfer Activity and Enzymatic Characterization of Pectic Polygalacturonate 4-α-Galacturonosyltransferase Solubilized from Pollen Tubes ofPetunia axillaris Using Pyridylaminated Oligogalacturonates as Substrates

Abstract: Polygalacturonate 4-␣-galacturonosyltransferase (pectin synthase) was solubilized from pollen tubes of Petunia axillaris and characterized. To accomplish this, an assay method using fluorogenic pyridylaminated-oligogalacturonic acids (PA-OGAs) as acceptor substrates was developed. When the pollen tube enzyme was solubilized with 0.5% (v/v) Triton X-100 and was incubated with PA-OGA and UDP-galacturonic acid (UDP-GalUA), successive transfer activity of more than 10 GalUAs from UDP-GalUA to the nonreducing end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…UDP-sugars formed in pollen tubes are probably utilized in the synthesis of cell-wall polysaccharides such as callose, pectins, and AGPs catalyzed by various glycosyltransferases. 28,29) On the other hand, we observed that AtUSP was expressed in many tissues other than pollen and pollen tube (Fig. 3), suggesting a housekeeping function for AtUSP rather than a special function confined to the development and germination of pollen.…”
Section: Discussionmentioning
confidence: 79%
“…UDP-sugars formed in pollen tubes are probably utilized in the synthesis of cell-wall polysaccharides such as callose, pectins, and AGPs catalyzed by various glycosyltransferases. 28,29) On the other hand, we observed that AtUSP was expressed in many tissues other than pollen and pollen tube (Fig. 3), suggesting a housekeeping function for AtUSP rather than a special function confined to the development and germination of pollen.…”
Section: Discussionmentioning
confidence: 79%
“…Polymeric pectins, such as poly-GalA and pectin, are less favorable substrates (21). Membrane-permeabilized GalAT activity from pumpkin yielded a population of OGAs elongated by up to five galacturonosyl residues (19), whereas the solubilized petunia enzyme added up to 27 galacturonosyl residues onto the OGA acceptors (18). Clarification of the mode of action of GalAT(s) and the mechanism of HG synthesis requires access to purified or recombinantly expressed enzyme(s).…”
mentioning
confidence: 99%
“…Establishment of conditions to recover detergentsolubilized GalAT activity from membrane fractions (17) and in vitro studies using radiolabeled substrate (17) or fluorescently tagged (18,19) acceptors established that, in vitro, GalAT preferentially transfers GalA onto the nonreducing end (20) of HG oligosaccharide acceptors [oligogalacturonides (OGAs)] of a degree of polymerization (DP) Ͼ9 (17,18), although OGA acceptors as small as a trimer can be used (18,19). Polymeric pectins, such as poly-GalA and pectin, are less favorable substrates (21).…”
mentioning
confidence: 99%
“…16) The enzyme has been characterized in a detergent-solubilized form of suspension cultures of tobacco cells 17) and petunia pollen tubes. 18) The activity was also detected in azuki bean 19) and pumpkin 20) in a detergent-permeabilized form. The solubilized enzyme y To whom correspondence should be addressed.…”
Section: -6)mentioning
confidence: 91%